SOURCE OF PROCYCLICALITY IN DUAL BANKING SYSTEM: THE CASE OF INDONESIA - Naahilah Hunafaa’ Al-Qudsy; Khoirul Umam (Journal of Islamic Economics and Philanthropy, 2020)
The global crisis in 2008 is driven by the credit bubble until leaves the impact of economy and financial sector in many countries, including Indonesia. The behaviour of banks in excessive lending is referred to procyclicality. If loans are not balanced with the needs of the economy, it will lead to imbalances in economic growth that could lead to a financial crisis. Theoretically, Islamic banking does not cause credit bubble because it is more allocate the financing to the real sector of economy. The purposes of this research are to know whether the level of procyclicality of conventional and Islamic banking in Indonesia, and to know the determinant of procyclicality of conventional and Islamic banking in Indonesia. The researcher uses a quantitative approach. This study uses time series data, which begin monthly from the year 2013M01 - 2017M12. The data is taken from the Economic and Financial Statistics Indonesia (SEKI-Bank Indonesia), the Central Statistics Agency (BPS), and the Financial Services Authority (OJK). The method of analyzing data is Vector Auto-regression (VAR) and Vector Error Correction Model (VECM). The results of this study indicate that conventional banking behave on procyclicality. On the contrary, Islamic banking does not behave procyclicality. The determinant of procyclicality on conventional banking in short-term is the Total Credit (CRE), and also in long term is the Total Credit (CRE). Then the determinant of procyclicality on Islamic banking in short-term is the Total Financing (FIN), while in long term is the Sharia of Bank Indonesia Certificates (SBIS).